A rare case of adult-onset blepharophimosis, ptosis, and epicanthus inversus syndrome: Case report (Indian Journal of Case Reports, 2019)
Blepharophimosis, ptosis, and epicanthus inversus syndrome (BPES) is a rare genetic condition caused by a mutation in the FOXL2 gene and it is inherited in an autosomal dominant pattern. Identification and diagnosis of BPES syndrome by an ophthalmologist are relatively easy, based on the characteristic ocular manifestations. The most common age group at the time of diagnosis is 4 to 8 years. Here, we present an unusual case of BPES in a patient who presented with the syndrome at the age of 52 years. There is a need for increased awareness about this condition among ophthalmologists as early diagnosis is the key factor in preventing long term complications.